Early communication development in infants and toddlers with Fragile X syndrome. (May 2022) - Mattie, Laura J; Hamrick, Lisa R
Background and Aims: Individuals with fragile X syndrome (FXS) characteristically struggle with language and communication throughout the life course, but there is limited research on the development of communication before 24 months. The purpose of this study is to describe the early communication of infants and toddlers with FXS using the Communication and Symbolic Behavior Scales-Caregiver Questionnaire (CSBS-CQ), a standardized communication screening measure, as compared to the reported normative data of the CSBS-CQ and identify the percentage of infants and toddlers who scored within the range of concern. Documenting how children with FXS perform on screening measures can provide a quick snapshot of skills to help clinicians determine the need for services. Methods: Participants were 22 infants and toddlers with FXS between 6 and 29 months. Performance on the CSBS-CQ was compared to the measure's normative data. The CSBS-CQ was completed by mothers, and children were administered the Mullen Scales of Early Learning. Because co-occurring autism is common in FXS, the presence of autism was determined using a clinical best estimate procedure. Results: Overall and within the domains and subdomains of the CSBS-CQ, infants and toddlers with FXS had significantly lower scores than the normative data. Further, 68.2% of our sample was in the range of concern for their overall communication score. The presence of autism led to consistently lower scores, and more infants and toddlers with FXS + autism scored within the range of concern. Conclusions: Our findings suggest that delays in early communication are evident in comparison to typically developing norms before 24 months. These findings also emphasize that infants and toddlers with FXS would likely benefit from early language intervention given that 68.2% of our sample was in the range of concern for their overall communication score. Implications: Early identification and developmental monitoring of children with FXS will help to determine concerns in communication and other domains of development. While early communication broadly may not be an early indicator of autism in FXS, some specific skills, such as eye gaze, may serve as such an indicator. Screening measures, like the CSBS-CQ, may help monitor both early communication impairments and autism symptoms. Infants and toddlers with FXS, regardless of autism status, will benefit from early language interventions.